Effect of Sunflower, Almond, and Rapeseed Oils as Additives on Thermal Properties of a Machinery Oil - José de Jesús Agustín Flores Cuautle; Oscar Osvaldo Sandoval González; Carlos Omar González Morán; José Pastor Rodríguez Jarquin; Citlalli Jessica Trujillo Romero; Gemima Lara Hernandez (Applied Sciences, 2021)
Vegetable oils are considered to be eco-friendly and to offer good lubricant properties; however, their low thermo-oxidative stability makes their use as a lubricant base challenging. In this research, sunflower, almond, and rapeseed vegetable oils were added in volumes of 5, 10, 15, and 20% to a machinery oil, and the thermal properties of the resulting fluids were studied. Sunflower, almond, and rapeseed oils were chosen considering their fatty acid composition and the tocopherol content. During this investigation, thermal diffusivity was measured by using the thermal wave resonance cavity technique, while thermal effusivity was determined by the inverse photopyroelectric method, and the obtained values ranged from 4.63 to 5.75 Ws1/2m−2K−1 × 102. The thermal conductivity was calculated by obtaining a complete thermal characterization. The results showed a linear relationship between the percentage of vegetable oil and the thermal diffusivity. It was also noted that the thermal properties of diffusivity and effusivity could be tuned when using almond, sunflower, and rapeseed oils in the appropriate percentages. Hence, the influence of vegetable oils on the thermal properties of lubricating oil were closely related to the number of fatty acids.